1995
DOI: 10.1128/aac.39.9.2013
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium deficiency induces joint cartilage lesions in juvenile rats which are identical to quinolone-induced arthropathy

Abstract: Quinolones accumulate in cartilage, and because they form chelate complexes with divalent cations, they possess the potential to induce a deficiency of functionally available magnesium. To test the hypothesis that quinolone-induced arthropathy is caused (or aggravated) by magnesium deficiency in cartilage, we induced magnesium deficiency by feeding juvenile rats a magnesium-deficient diet for 9 days and treated the rats with single oral doses of ofloxacin (0, 100, 300, 600, or 1,200 mg/kg of body weight) durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 25 publications
10
64
0
5
Order By: Relevance
“…Ciprofloxacin induced chrondrotoxicity was also explain on the basis that Ciprofloxacin chelates magnesium ions or divalent ions resulting in change function of chondrocytes surface integrin receptors (Stahlmann et al, 1995;Shakibaei et al, 2000;Lozo et al, 2004). This report is supported by the ability of magnesium to reverse or inhibit Ciprofloxacin induced chrondrotoxicity (Stahlmann et al, 1999;Stahlmann, 2002).…”
Section: Pathogenesissupporting
confidence: 58%
“…Ciprofloxacin induced chrondrotoxicity was also explain on the basis that Ciprofloxacin chelates magnesium ions or divalent ions resulting in change function of chondrocytes surface integrin receptors (Stahlmann et al, 1995;Shakibaei et al, 2000;Lozo et al, 2004). This report is supported by the ability of magnesium to reverse or inhibit Ciprofloxacin induced chrondrotoxicity (Stahlmann et al, 1999;Stahlmann, 2002).…”
Section: Pathogenesissupporting
confidence: 58%
“…The lesion seen in the present study was the same as those previously reported. Although its mechanisms are not completely understood, some suggested hypotheses include the involvement of mitochondrial dysfunction (2), interference of the drug with DNA metabolism (30), or interference with the extracellular matrix of joint cartilage by formation of quinolone-magnesium chelate complexes (5,27 Quinolones have been widely used. However, because of their toxic potential to the immature articular cartilage, which has been demonstrated in many animal species (2,6,7,14,16,26) …”
Section: Electron Microscopymentioning
confidence: 99%
“…Quinolones are potent chelating agents (16,17,20) and there is emerging evidence that they damage juvenile joint cartilage of animals due to their chelating properties, in particular by forming stable chelate complexes with magnesium (24,27). In this respect, it is of interest that lameness and gait alterations closely resembling quinolone-induced arthropathy were described in magnesiumdeficient dogs almost 4 decades ago (26).…”
Section: Integrin Stainingmentioning
confidence: 99%